PEMBUATAN MEDIA PEMBELAJARAN MUATAN LOKAL PETERNAKAN PADA MI HIDAYATUL INSAN KARANGANYAR - Oktyajati, Nancy; Fitroh, Bagus Andika; Rois, Dimas Ilham Nur; Malik, Muhammad Munib Khusni; Bila, Ica Salsa (Jurnal Abdimas Bina Bangsa, 2024)
Madrasah Ibtidaiyah Hidayatul Insan in Karanganyar has a mission to shape a generation of Huffadz (Qur'an memorizers), Tujjar (Muslim entrepreneurs), Ahlul Ilmi (Muslim scholars), and Rijaalul Ummah (community leaders) through an educational approach based on nature and social engagement. As part of its efforts to equip students with entrepreneurial skills, MI Hidayatul Insan developed an agribusiness program focusing on agriculture and livestock. One of the main challenges is the lack of human resources in the livestock sector, as well as insufficient supporting infrastructure. Therefore, a higher education institution collaborated with MI HI in a program to provide learning media, including the supply of an automatic incubator and training for teachers. This program aims to enhance students' livestock competencies and support the sustainability of the livestock sector in the future. The initial results of this program showed a 52% hatching rate, below the 80% target, but evaluations have been conducted for future improvements. This activity also supports the implementation of project-based learning for university students through the MBKM program